The year of the three sisters - Cheng, Andrea (Cheng, Andrea. Anna Wang novel, 2015)
Twelve-year-old Anna's friend Andee spearheads a campaign to bring Fan from China to Cincinnati on a year-long cultural exchange, but before Fan even arrives Anna's concerned that Andee and Fan are too different to get along.